Relação entre cobertura superficial e piezometria em encosta com processo de erosão em túneis e voçoroca no leste de Cascavel (PR) - Bazzotti, Diego Maikon (2013)
The tunnel erosion is a specific form of de subterranean erosion. The study area is located in the municipality of Cascavel, in district of São João do Oeste. This work has objective to know the relation between surface coverage and the piezometric in slope with gullye and tunnel erosion processes. The thecniques used were elaboration of geologic profile and transects. It was used also monitoring the piezometric data associated with rainfall to understand the behavior of hydrological parameters of the slope. The results indicated that the material that covers the slope has sandy-clay. The textural proprieties contribute to the expansion of the tunnel; the Unit 3 is the layer that promotes largest circulation of water in slope. The upper units are the keepers of the piezometric levels of the slope. The development of the tunnel is intrinsically related to the hydrological, topographical and kind and distribution of the surface materials in slope, which provide the installation and development of subsurface erosion mechanisms. Therefore, the factors that contribute to the genesis and evolution of the tunnel into the Bazzotti slope express the dynamics in the evolution of the gully, which molds the relief over the year. The study area is located Rattlesnake, in the district of St. John West d. The focus of the work aimed at understanding the relationship between surface coverage and piezometric in slope erosion process in tunnels and gullies. The techniques used in the research were constructing of the geological profile and transects. It was used also monitoring the piezometric associated with rainfall to understand the behavior of hydrological parameters of the slope.